2011
DOI: 10.1021/ja206099t
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Carbohalogenation: Bromide to Iodide Exchange and Domino Processes

Abstract: Aryl bromides have been used to prepare a variety of nitrogen- and oxygen-containing heterocycles featuring new carbon-carbon and carbon-iodine bonds. This palladium-catalyzed carbohalogenation requires potassium iodide for the reaction to proceed in high yields. Additionally, the first examples of domino carbohalogenation reactions have been demonstrated using both aryl iodide and aryl bromide starting materials. Complex products with multiple rings and stereogenic centers are generated in excellent yields wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(69 citation statements)
references
References 34 publications
2
67
0
Order By: Relevance
“…449 The authors also reported the cyclization of polyunsaturated aryl iodides which provided access to complex polycyclic scaffolds with the retention of the reactive functionality. For example, fused lactam 445 could be obtained in 91% in 5:1 dr or 89% in 3:1 dr from the corresponding aryl iodide 443 or aryl bromide 444, respectively (Scheme 287).…”
Section: Synthesis Of Alkyl Halidesmentioning
confidence: 99%
“…449 The authors also reported the cyclization of polyunsaturated aryl iodides which provided access to complex polycyclic scaffolds with the retention of the reactive functionality. For example, fused lactam 445 could be obtained in 91% in 5:1 dr or 89% in 3:1 dr from the corresponding aryl iodide 443 or aryl bromide 444, respectively (Scheme 287).…”
Section: Synthesis Of Alkyl Halidesmentioning
confidence: 99%
“…As discussed earlier, the palladium-catalyzed couplings of alkenyl halides with alkenes can give rise to the formation of π-allylpalladium complexes, which can then be attacked by internal nucleophiles including hydroxy groups to yield various oxacyclic systems (Scheme 8.38) [343]. Lautens et al [344] reported the termination of a cascade of two intramolecular Heck 5-exo-trig carbopalladations by iodide leading from the o-bromobenzamide derivative 159 in the presence of potassium iodide to the heterotricycle 160 in 88% yield (Scheme 8.39). The same transformation was observed for the o-iodo analog of 159 and other o-iodophenyl derivatives with alkenyl side chains leading to various benzannelated dihydrofuran and dihydropyrrole derivatives.…”
Section: Palladium-catalyzed Reactions Involving Nucleophilic Substratesmentioning
confidence: 99%
“…Scheme 8.39Termination of a two-step 5-exo-trig carbopalladation cascade by reductive elimination from an alkylpalladium iodide intermediate[344].…”
mentioning
confidence: 99%
“…[10] However, no useful quantity of carbobromination product was obtained under the previous standard conditions. The reaction afforded a 95 % yield of iodide 3 when two equivalents of KI were added (Scheme 5).…”
Section: Sp 3 -Carbon-halogen Bond Formationmentioning
confidence: 99%